The Influence of Price Bundling, Physical Evidence, and Store Atmosphere on Consumer Buying Decisions - Fitriani, Amalia; Hanif; Supriyaningsih, Okta (Research Horizon, 2025)
This study aims to analyze the influence of Price Bundling, Physical Evidence, and Store Atmosphere on Consumer Purchasing Decisions. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique. Each independent variable Price Bundling, Physical Evidence, and Store Atmosphere were measured using specific indicators. Data was collected through questionnaires using a five-point Likert scale. The sampling technique used was non-probability sampling with a total of 100 respondents. The findings reveal that Price Bundling has a positive but insignificant effect on consumer purchasing decisions. In contrast, Physical Evidence and Store Atmosphere both have a positive and significant effect on purchasing decisions. These results suggest that although price bundling strategies provide a positive perception, they are not strong enough to significantly influence consumer decisions. On the other hand, visual elements and the store’s atmosphere are more effective in encouraging consumers to make purchases. This highlights the importance of creating an appealing environment and enhancing tangible elements to attract and retain buyers.